2020
DOI: 10.1177/0268355519897650
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in the frequency of venous thromboembolism: An updated result of a meta-analysis and systemic review

Abstract: Objective Venous thromboembolism, including deep vein thrombosis and pulmonary embolism, is likely to cause the death of both medical and surgical patients. Despite some evidence of seasonal variation in the incidence of venous thromboembolism, the existing studies obtain contradictory results. A temporal pattern for pulmonary embolism is known, but data on deep vein thrombosis are inconclusive. The purpose of this study is to make a meta-analysis and systematically review the literature about seasonal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(60 reference statements)
2
6
0
3
Order By: Relevance
“…When compared to summer, there was a greater incidence of AF in winter (OR:1.22; 95% CI:1.02–1.45) [ 4 ], spring (OR:1.20; 95% CI:1.02–1.42), and fall (OR:1.28; 95% CI:1.08–1.51). Spring admissions had a greater risk of VTE than summer admissions [(OR:1.54; 95% CI:1.09–2.16) vs. summer; p = 0.067] which is what was reported by Zhao H et al [ 6 ]. Other outcomes, such as all-cause mortality and cardiogenic shock, were not associated after controlling for confounding variables.…”
supporting
confidence: 74%
“…When compared to summer, there was a greater incidence of AF in winter (OR:1.22; 95% CI:1.02–1.45) [ 4 ], spring (OR:1.20; 95% CI:1.02–1.42), and fall (OR:1.28; 95% CI:1.08–1.51). Spring admissions had a greater risk of VTE than summer admissions [(OR:1.54; 95% CI:1.09–2.16) vs. summer; p = 0.067] which is what was reported by Zhao H et al [ 6 ]. Other outcomes, such as all-cause mortality and cardiogenic shock, were not associated after controlling for confounding variables.…”
supporting
confidence: 74%
“…Incidence rate ratios (IRRs) with 95% confidence intervals (95% CIs) were calculated for each stratum of the exposed period compared with the baseline period (12). We adjusted for season and age (2-year age bands) to account for the seasonal trend of gout flares and VTE (21,22), and increasing incidence of gout flares and VTE with age (23,24). Supplementary Material S2 shows the sample size estimation (available on the Arthritis & Rheumatology website at https://onlinelibrary.wiley.com/doi/ 10.1002/art.42480).…”
Section: Methodsmentioning
confidence: 99%
“…There is an observation that hypobaric exposure activates coagulation [71]. However, based on the results of publications [72][73][74][75] included in the meta-analysis Zhao et al [76], investigating the seasonal dynamics of thromboembolism, it can be concluded that in regions with low atmospheric pressure in summer (China, Korea), thromboembolism occurs more often in winter than in summer. It was shown that in addition to cholesterol and hematocrit, levels of blood coagulation factors increase in winter compared to summer [77][78][79].…”
Section: Discussionmentioning
confidence: 99%